Macron’s Euphemism and Speech Acts in Prophet Cartoons Political Interview Used for Teaching Reading Comprehension - Fitri Rahmawati Astiandani; Slamet Setiawan; Ali Mustofa (Institut Agama Islam Negeri Palopo, 2021)
The prophet’s cartoon is an immense controversy for France and a country with a Muslim majority. As the France President, Emmanuel Macron has rarely gained critic toward the use of language when conveying his political discourse in the prophet cartoon case. Thus, this study explores Macron’s euphemism expressions in his political interview with Al Jazeera on the prophet cartoon. This paper also examines the effect (perlocutionary act) of Macron’s euphemism and then uses them as a means of teaching inferential reading comprehension in secondary school. This qualitative study employed transcription and documentation techniques to obtain the data. Macron’s euphemism was taken from his political interview on October 31, 2020 with Al-Jazeera, and comments of Macron’s political interview on YouTube are also used for the sample of the perlocutionary act. Moreover, Macron’s euphemism in YouTube is associated with euphemism in Jakarta Post online newspaper to be used as a means of teaching inferential reading comprehension. This study relied on the kind of euphemism by Rawson (1981), euphemism formation by Šebková (2012), perlocutionary act by Austin (1962), and inferential reading theory by Westwood (2008). In brief, it has been found that Macron utilized many positive euphemisms with widening formation to maintain his ideology and to shape the views of the world’s Muslims. Two perlocutionary acts (expression of acceptance and rejection) were also discovered, and Macron’s euphemism could be used as a means of teaching inferential reading comprehension.